Comparisons of isoflavones from Korean and Chinese soybean and processed products - Lee, Youn-Woo; Kim, Jae-Duck; Zheng, Jinzhu; Row, Kyung Ho (ELSEVIER, 2007)
Soybeans and soy products are the main source of isoflavones. Several methods and different kinds of soybeans have been published to quantify soy isoflavones, but the amount of isoflavones was variable each other. In order to investigate the contents of isoflavone with pure and processed soybean (the name of soybean is Dae du soybean) from different area (Korea and China), some isoflavones (7-o-glucosides, acetyl daidzin, malonyl genistin and aglycones) from Korean soybean, Chinese soybean and their processed products of soybeans were extracted by 60% EtOH, and analyzed using reversed-phase high performance liquid chromatography (RP-HPLC). The malonyl genistin was found the most content in soybean, but it was very small in chungkukjang. For the aglycones, glycitein was extracted more than daidzein from chungkukjang, contrary to the trend in pure soybean. The small amounts of isoflavones were extracted from doenjang, and the main isoflavone was daidzein. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: SOY; PHYTOESTROGENS; EXTRACTION